CREATIVITY AND INNOVATION IN CULTURE: AN EFFORT TOWARDS INTERPRETING THE PHILOSOPHY AND CULTURAL STUDIES OF M. K. PETROV - Rimskiy, Viktor; Borisov, Sergey; Borisova, Oksana (Revista Inclusiones, 2020)
The topic of the study is relevant due to the fact that innovations in culture (social and technological, scientific and educational, works of art and literature ones) and emerging new technologies based on them are still not sufficiently explicated, although innovations determined the historical and cultural evolution of different societies in the past as well, and they still determine the economic and sociocultural dynamics of mankind nowadays. Innovative changes had and have both positive, revolutionary, and sometimes negative, destructive effects. The main goal of the article is to give author’s own interpretation of the ideas of Mikhail Petrov (1923-1987) - a front-line soldier, a remarkable Soviet writer and translator, an outstanding scientist and philosopher who laid the foundations of Russian cultural studies, the sociology of science and education, innovation and the systematic approach in regionalistics and science.